Developing and implementing a computer-adaptive test for english: The SLUPE experience - Burston, Jack (My University, 2016)
When the granting of a degree depends upon the successful completion of an EFL course requirement, it is critically important to identify weak students as soon as possible in order to provide them with counselling and self-study guidance. To improve diagnostic efficiency, we adopted the freely available SLUPE (Saint Louis University Placement Exam) authoring system to create a computer-adaptive test for English (E-CAT). Following initial pilot testing with nearly 200 students during the Spring of 2013, the E-CAT was administered to a full cohort of some 450 first-year students during the Fall semester of 2013 and again to 350 students in the Spring of 2014. The placement results of the E-CAT were compared to student self-evaluations and instructor ratings. Of the three, E-CAT placements correlated most closely with instructor ratings. Given these satisfactory results, we now base our diagnostic testing entirely upon the E-CAT. We can, thus, confirm that the SLUPE platform will provide anyone wanting to create a computer-adaptive test with the means of doing so. Notwithstanding, the actual preparation of questions is time consuming and requires several iterations based on the statistical analysis of student responses in order to objectively determine question difficulty levels.
Keywords: CAT; Computer-adapted testing; EFL; English; Placement